Factors associated with unquantifiable total HIV-1 DNA in peripheral blood in persons living with HIV: An observational study - Aurélie Ram; Vanessa Rascon Velasco; Gilbert Mchantaf; Véronique Avettand-Fénoël; Jean-Paul Viard (Elsevier, 2024)
Background: The human immunodeficiency virus type 1 (HIV-1) cannot be eradicated even with suppressive antiretroviral therapy because its retrotranscribed genome integrates into the DNA of host cells, creating a long-term reservoir. Quantification of total HIV-1 DNA in peripheral blood is a biomarker of this reservoir that can predict progression of the infection, treatment response, and HIV-1-related complications. A deeper understanding of the reservoir may help develop a cures. Objective: This study aimed to characterize persons living with HIV-1 (PLWH) with unquantifiable total HIV-1 DNA in blood (below the quantification threshold) and identify associated factors. Methods: We have conducted a retrospective observational study. During the study period, all PLWH who had total leukocyte-associated HIV-1 DNA measured by quantitative PCR were included. We have isolated a population of participants with HIV-1 DNA levels below the quantification threshold (40 copies/106 leukocytes). Results: Out of 1094 patients analysed, 62 had unquantifiable and 1032 quantifiable HIV-1 DNA levels in blood. We have found that those with unquantifiable HIV-1 DNA had a higher CD4 T cell nadir (p = 0.006) and a lower viral load zenith (p < 0.001). Multivariate analyses showed that initiation of treatment in primary infection was the only protective factor against HIV-1 DNA quantifiability, the odds of HIV-1 DNA quantifiability decreased by 82% in those treated within 30 days of infection, after controlling for other factors. Conclusion: Our research highlights the importance of an early start of anti-retroviral therapy to limit the size of the HIV-1 reservoir, as receiving treatment during primary infection was found as the only protective factor against quantifiability of HIV-1 DNA in blood.